Analysis of Healthcare Interventions that Change Patient Trajectories - Bigelow, James H. (RAND Corporation, 2005)
Examines interventions in the healthcare system that use Electronic Medical Record Systems (EMR-S) to affect patient trajectories--i.e., the sequence of encounters a patient has with the healthcare system--by improving health and thereby reducing healthcare utilization, or by reducing a costly form of utilization (e.g., inpatient stays) and increasing a more economical form (e.g., office visits to physicians, or prescription medications).